2006
DOI: 10.1007/s10705-005-6241-9
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Nitrate Leaching to Groundwater in an Intensive Dairy Farming System

Abstract: Dairy farming is one of the main contributors to nitrate leaching to groundwater, particularly on soils that are susceptible to leaching, such as light well-drained sandy soils. In the Netherlands, as in many other European countries, these soils are predominantly used for dairy farming. A prototype dairy farming system that has been implemented in practice in 1989 has continuously been adapted since then to meet environmental standards (i.e. the EU-standard of 50 mg NO 3 À l À1 ) without reducing milk product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 36 publications
1
26
1
2
Order By: Relevance
“…However, less information in regard to N leaching is available for tropical and sub-tropical, undeveloped agricultural regions. Nitrate produced through nitrification processes in the upper layers can subsequently move downward and accumulate in deeper layers [64,65]. However, in our study, no statistical difference was found for dissolved nitrogen in the form of nitrates (NO3-N) in the whole soil profile (0-120 cm) (Data not shown).…”
Section: Relative Nitrogen Uptake Efficiency and Potential For Nitratcontrasting
confidence: 75%
“…However, less information in regard to N leaching is available for tropical and sub-tropical, undeveloped agricultural regions. Nitrate produced through nitrification processes in the upper layers can subsequently move downward and accumulate in deeper layers [64,65]. However, in our study, no statistical difference was found for dissolved nitrogen in the form of nitrates (NO3-N) in the whole soil profile (0-120 cm) (Data not shown).…”
Section: Relative Nitrogen Uptake Efficiency and Potential For Nitratcontrasting
confidence: 75%
“…Evidence for a decrease in grazing are the increased mowing percentage by a factor 1.7 (LMM data not shown) and the decreased ammonia emission during grazing, from 13.1 million kg in 1990 to 0.8 million kg in 2012 (CBS 2014). Lower nitrate concentrations in grass cutting systems than in grass grazing systems were reported by others (Nevens & Rehuel 2003;Verloop et al 2006). Hansen et al (2012) showed that urinations of ruminants on grazed pastures increased the risk of nitrate leaching.…”
Section: Relationship Between Nlf and N Surplus/timementioning
confidence: 69%
“…The upper metre of groundwater in this region, sampled in the period April-October represents water leached from the root zone reflecting mainly the agricultural practices of the previous agricultural year (Boumans et al 2001). However, Verloop et al (2006) showed that the nitrate concentration in the upper groundwater was also influenced by Year specific long-term median precipitation surplus based on fractions of crop types, soil types and GRCs (overlays with maps) and crop type, soil type and GRC specific long-term median precipitation surplus (Van Bakel et al 2008). agricultural practices of earlier years for a forage maize-grass rotation at an experimental farm with groundwater level between 1 and 3 m below soil surface level (m-SSL).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…One of the loss pathways in the nitrogen cycle is nitrate leaching from the soil. The magnitude of leaching also strongly varies, depending on such factors as soil type, cropping system, weather conditions, and fertilizer regime (Di and Cameron 2002;Hauggaard-Nielsen et al 2003;Verloop et al 2006). High leaching losses from intensive agriculture may cause high nitrate concentrations in groundwater, which potentially carries health risks.…”
mentioning
confidence: 99%